Continuity and change in the northeastern Sertão of Brazil - Hoefle, SW (1983)
This work deals with cultural change in the semi-arid Sertão of Northeast Brazil. Since 1940, the Sertanejo way of life has undergone considerable modification provoked by a process of increasing economic and cultural integration into the national society. The hardships caused by recurrent drought have been reduced and widescale famine no longer occurs. Also, improved transport facilities, together with new market opportunities, have enabled the limited introduction of irrigation and intensification of stock-raising. These activities are less susceptible to drought but dry farming has been little changed and crop failure is still frequent. This, combined with increasing population pressure and low produce prices, have depressed farming. Monetarization of the local economy caused growth in other sectors but this was offset by greater unemployment problems created by large-scale substitution of local crafts by manufactured goods. Hence, emigration continues, although drought is no longer the principal cause. Landless peasants have left the country, thus lessening class disparity here but only shifting it to town. The urban upper classes increasingly accept the national lifestyle and the poor have improved their lot, but the gap between the two is growing. The kinship system has become more bounded because of the effects of monetarization and the shift away from a rural lifestyle. However, concepts of family honour and morality have changed little and feuding persists. Political power has shifted from rural to urban groups but leaders are descendants of the traditional families of the past. The structure of the political system, with strict control of higher level politicians over county leaders and the latter over the local people, remains intact. New religious sects have been introduced and are related to increasing urbanisation. Protestant and Afro-Brazilian sects appeal to some dissatisfied urban merchants and poor labourers but the sects have encountered many obstacles to wider acceptance and so the majority. of Sertanejos are still Catholics.